Global inequality in national food supplies and diet-related health outcomes, 1970–2010 (P04-094-19) - Bell, Winnie; Lividini, Keith; Masters, William A. (Oxford University Press, 2019)
The global food system has changed rapidly over recent decades, with large shifts in agricultural supply conditions, international trade, food manufacturing and nutrient availability. These shifts have contributed to both positive and negative impacts on health and wellbeing with some countries catching up while others have fallen further below international norms. We aim to quantify long-run changes in the food supply and diet-related health disparities across countries, to illustrate how inequality has changed from the 1970 s to the 2010 s.